Efficacy of application of vaccine AI H5N1 clade 2.1.3 on Mojosari ducks challenge against AI H5N1 clade 2.3.2 in laboratory conditions - R, Indriani; NLPI, Dharmayanti; R.M.A., Adjid (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Influenza virus HPAI H5N1 clade 2.3.2 outbreaks since September 2012 caused high mortality in ducks. Vaccination is one of strategies recommended by government. However, AI H5N1 clade 2.3.2 vaccine not yet available during this research, while AI H5N1 clade 2.1.3 vaccines available in markets. Therefore it was important to do study on efficay of HPAI H5N1 clade 2.1.3. vaccines on duck at laboratory scale. Three groups of Mojosari duck were used in this study, they were 1 group vaccinated with A Vaccine, 1 group vaccinated with B Vaccine, and 1 group as control (not vaccinated). Vacination groups consisted of 9 DOD and control group was consisted of 6 DOD. Vaccination was conducted when the duck at three weeks old of age using single dose recommended by producer. At three weeks later (ducks at 6 weeks old of age) all Groups of ducks were challenged with virus HPAI H5N1 clade 2.3.2 at dose 106 EID50/ml by drops intranasaly. Result showed that Group 1 (vaccinated with A Vaccine) produced 67% protection (3 out of 9 ducks died), Group 2 (vaccinated with B Vaccine) produced 100% protection (non out of 9 ducks died), and Group 3 (control, not vaccinated) produce 0% protection (all of 9 ducks died). This study give an alternative of choise to use AI H5N1 Clade 2.1.3 vaccine with high protection when AI H5N1 Clade 2.3.2 vaccine not available in markets to controll high mortality in ducks caused by HPAI H5N1 clade 2.3.2 outbreaks. Key Words: Duck, HPAI, AI, Avian Influenza, Vaccine